Pengaruh Harga, Kualitas Produk, Dan Kualitas Pelayanan Terhadap Loyalitas Pelanggan Di CV Tri Jaya Mobil Tiban Batam - Harianja, Josepin (Tractare: Jurnal Ekonomi-Manajemen, 2023)
This study aims to determine the effect of price, product quality, and service quality bothpartially and simultaneously on customer loyalty at CV Tri Jaya Mobil Tiban Batam. Thisresearch was conducted using quantitative research methods with a total of 100 respondents anddata collection using a questionnaire. The results of data processing on the price variable foundthat the tcount was 3.288 < t table of 1.660 with a significant level of 0.001> 0.05, so the pricehas a positive and significant effect on customer loyalty. The product quality variable produces atcount value of 5.728> t table of 1.660 with a significant level of 0.000 t table 1.660 with asignificant level of 0.000 ftabel 2.69 with a significant value of 0.000Keywords : Price, Product Quality, Service Quality, and Customer Loyalty